European Integration : Historical Trajectories, Geopolitical Contexts - Arnason, Johann P. (Annual of European and Global Studies : AEGS, 2022)
Explores the historical, geopolitical and conjunctural aspects of European integration, and their relevance to understanding the current crisisBrings long-term perspectives to bear on postwar and post-2000 developments of European affairsAnalyses the overall dynamics of the present crisis, as well as the impact of particular actors and factorsDiscusses the specific problems of peripheries of the EU, especially East Central Europe, underlining the need for a broader Eurasian perspectiveIncludes a comparison of the Habsburg Empire and the EU, plus discussions of efforts to constitutionalise the EU and Islam in contemporary EuropeTo understand the current difficulties and future prospects of European integration, multiple perspectives are required. The essays in this collection explore historical and geopolitical aspects of European integration and their relevance to interpretations of the current climate. They also examine the different regional dynamics of integration and the attitudes that result from those experiences, including in the European peripheries that are so often overshadowed by the dominant centres. In drawing all of these perspectives together, the collection allows the reader to assess the EU's current crisis in context.ContributorsJohann P. Arnason, La Trobe University, Australia, and Charles University, Czech Republic. Paul Blokker, University of Bologna, Italy, and Charles University, Czech Republic. Natalie J. Doyle, Monash University, Australia. Chris Hann, Max Planck Institute for Social Anthropology in Halle, GermanyToby E. Huff, Harvard University and University of Arizona, USA.Ireneusz Pawel Karolewski, University of Wroclaw, Poland.Helmut Kuzmics, University of Graz, Austria (retired). Dennis Smith, Loughborough University, UK. Bo Stråth, University of Helsinki, Finland.